2012
DOI: 10.1007/s11748-011-0849-2
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for atrial fibrillation: recent progress and future perspective

Abstract: Development and introduction of radiofrequency ablation devices allowed the maze procedures to be performed safely and easily, further enabling off-pump pulmonary vein isolation through a mini-thoracotomy or thoracoscope. The effects of the maze procedure include prevention of stroke and other complications related to atrial fibrillation, improved cardiac performance, and relief of symptoms. Indications for the maze procedure have been discussed on the basis of the evidence. Pulmonary vein isolation has been s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…Pokushalov et al 74 reported success rates of < 40% at one year after performing isolated GP ablation for symptomatic, drug refractory persistent AF; circumferential isolation of the PVs was needed in these patients to increase the success rate of GP ablation. Recent surgical studies have also attempted to add GP ablation/excision to PV isolation, albeit with varying efficacy 69, 70, 80, 81 . However, it is clear while minimally invasive surgery consisting of bipolar radiofrequency pulmonary vein (PV) isolation and limited GP ablation is effective in reducing atrial fibrillation (AF) in patients with paroxysmal AF, it is less effective in those with persistent AF or long-standing persistent AF 82 .…”
Section: Selective Autonomic Denervation Of the Atria—a New Therapeutmentioning
confidence: 99%
“…Pokushalov et al 74 reported success rates of < 40% at one year after performing isolated GP ablation for symptomatic, drug refractory persistent AF; circumferential isolation of the PVs was needed in these patients to increase the success rate of GP ablation. Recent surgical studies have also attempted to add GP ablation/excision to PV isolation, albeit with varying efficacy 69, 70, 80, 81 . However, it is clear while minimally invasive surgery consisting of bipolar radiofrequency pulmonary vein (PV) isolation and limited GP ablation is effective in reducing atrial fibrillation (AF) in patients with paroxysmal AF, it is less effective in those with persistent AF or long-standing persistent AF 82 .…”
Section: Selective Autonomic Denervation Of the Atria—a New Therapeutmentioning
confidence: 99%
“…Increasing LA size was a significant risk factor for failure of a Maze procedure, and extensive size reduction or expanded lesion sets may be required in patients with a large LA [8]. LA volume reduction procedures have demonstrated an improved conversion rate of AF and increased the LA function postoperatively [4].…”
Section: Discussionmentioning
confidence: 99%
“…Karitsis et al (104) and others (105) demonstrated that when GP ablation was combined with PV isolation, it yielded better results than PV isolation alone, with success rates approaching 80% (104). Recent surgical studies also attempted to add GP ablation and/or excision to PV isolation with varying efficacy (97,98,106,107). The efficacy and durability of this approach has not been established.…”
Section: Role Of Autonomic Dysfunction In Creating a Vulnerable Substrate For Atrial Fibrillationmentioning
confidence: 99%